Identification and semi-quantification of Atlantic salmon in processed and mixed seafood products using Droplet Digital PCR (ddPCR). (August 2021) - Deconinck, Dumas; Hostens, Kris; Taverniers, Isabel; Volckaert, Filip A.M.; Robbens, Johan; Derycke, Sofie
Abstract: Fishery products are often subject to substitution fraud, which is hard to trace due to a lack of morphologic traits when processed, gutted, or decapitated. Traditional molecular methods (DNA barcoding) fail to identify products containing multiple species and cannot estimate original weight percentages. As a proof of concept, an Atlantic salmon ( Salmo salar ) specific ddPCR assay was designed to authenticate mixed food products. The method proved to be specific and able to accurately quantify S. salar when using DNA extracts, even in the presence of DNA from closely related salmon species. The ddPCR estimates correlated well with the percentage of S. salar in artificially assembled tissue mixtures. The effect of common salmon processing techniques (freezing, smoking, poaching with a "Bellevue" recipe and marinating with a 'Gravad lax' recipe) on the ddPCR output was investigated and freezing and marinating appeared to lower the copies detected by the ddPCR. Finally, the assay was applied to 46 retail products containing Atlantic or Pacific salmon, and no indications of substitution fraud were detected. The method allows for a semi-quantitative evaluation of the S. salar content in processed food products and can rapidly screen Atlantic salmon products and flag potentially tampered samples for further investigation. Highlights: A species-specific assay for Atlantic salmon with a low limit of detection was designed using ddPCR. The method was validated by testing selectivity, limits of quantification and detection, and the effects of processing. The method was successfully applied to retail samples without evidence of fraud. The method can identify and semi-quantify S. salar specific tissue in processed food products containing multiple species.